ANALISIS TREN PENDAPATAN ASLI DAERAH PEMERINTAH KOTA MANADO - Pesik, Jessica A. P.; Saerang, David P. E.; Manosoh, Hendrik Ch. (Universitas Sam Ratulangi, 2020)
Regional independence in the implementation of regional autonomy and fiscal decentralization is an issue faced by every Regional Government, because regional needs (fiscal need) that are not balanced with fiscal capacity (fiscal capacity) will lead to fiscal gap (fiscal gap). Local Government is demanded to be able to increase PAD without violating norms by optimizing the existing potential. The main indicator of the progress of a region is through the economic growth of the region. This is illustrated from the economic growth rate of Manado City to be one of the regions that has experienced a significant increase in PAD and economic growth. The purpose of this study is to analyze the contribution of local taxes and regional levies on local own-source revenues, the effectiveness of PAD and the degree of fiscal decentralization in Manado City in 2012-2018 and trends during 2019-2025. The method of data analysis used in this study is the method used in this study is research by combining two forms of research namely qualitative research and quantitative research. The results of the study that the trend of the contribution of local taxes and levies on local revenue tends to decrease while the effectiveness trend and the degree of fiscal decentralization has increased.Â Keywords: Trend, Contribution, Effectiveness, Degree of Fiscal Decentralization, PAD,